Actualización modelo empresa familiar responsable “efr” norma 1000-1 a la 1000-2 en la empresa veolia aguas de Tunja s.a.- e.s.p. (2021)
Veolia is a company certified since 2013 by the most family foundation in the EFR model "responsible family-minded company" this model comes from Spain, to grant the certification of personal and family work-life balance, allowing employees to feel committed to the company, improving their job performance.